Comparative Assessment of Microleakage in Various Bulkfill Flowable Composites: An In Vitro Study - Aishwarya Arya; Bobbin Gill; Nirmala Bishnoi; Dishanki Vishwanadulwar; Dron Lakhani; Aishwarya Bhatnagar (Journal of Pharmacy and Bioallied Sciences)
Aim and Objectives: To evaluate microleakage among three bulkfill flowable composites and a conventional packable composite. Material and Methods: 60 extracted molars were selected and randomly divided into four groups of 15 teeth each (Group A-Control group; G-Aenial, Group B-SDR Plus, Group C-Tetric EvoFlow, Group D-EverX Flow Bulkfill flowable composite). MO and DO cavities of specified dimensions were prepared with margins 1 mm below CEJ. Restorations in Group A were placed incrementally while in Groups B, C and D were bulkfilled (4 mm) followed by a capping layer of G-Aenial. The teeth were immersed in 1% methylene blue dye, sectioned mesiodistally and observed under stereomicroscope. Result: Group B showed the least microleakage followed by Groups A, C, and D, respectively. The difference between both restoration techniques was insignificant. Conclusion: All the bulkfill flowable composites and incrementally placed composite resulted in a comparable reduction of microleakage.